Experiences of Norwegian Mothers Attending an Online Course of Therapeutic Writing Following the Unexpected Death of a Child - Lehmann, Olga V.; Neimeyer, Robert A.; Thimm, Jens; Hjeltnes, Aslak; Lengelle, Reinekke; Kalstad, Trine Giving (Frontiers in Psychology, 2022)
The unexpected death of a child is one of the most challenging losses as it fractures survivors’ sense of parenthood and other layers of identity. Given that not all the bereaved parents who have need for support respond well to available treatments and that many have little access to further intervention or follow-up over time, online interventions featuring therapeutic writing and peer support have strong potential. In this article we explore how a group of bereaved mothers experienced the process of participating in an online course in therapeutic writing for the integration of grief. Our research questions were: How do parents who have lost a child experience being part of an online course in therapeutic writing? What are the perceived benefits and challenges of writing in processing their loss? We followed an existential phenomenological approach and analyzed fieldwork notes (n= 13), qualitative data from the application and assessment surveys (n= 35; n= 21), excerpts from the journals of some participants (n = 3), and email correspondence with some participants (n = 5). We categorized the results in three meaning units: 1. Where does my story begin? The “both and” of their silent chaos; 2. Standing on the middle line: a pregnancy that does not end; 3. Closures and openings: “careful optimism” and the need for community support. Participants experienced writing as an opportunity for self-exploration regarding their identities and their emotional world, as well as a means to develop and strengthen a bond with their lost child. They also experienced a sense of belonging, validation, and acceptance in the online group in a way that helped them make sense of their suffering. Online writing courses could be of benefit for bereaved parents who are grieving the unexpected loss of a child, but do not replace other interventions such as psychotherapy. In addition to trauma and attachment informed models of grief, identity informed models with a developmental focus might enhance the impact of low-threshold community interventions and more intensive clinical ones. Further studies and theoretical development in the area are needed, addressing dialogical notions such as the multivoicedness of the self.